Study of the use of hydroxyurea by patients with hemoglobinopathies assisted by the specialized component of Pharmaceutical Assistance in Piauí, Brazil (Research, Society and Development, 2020)
A study was conducted on the use of the hydroxyurea drug dispensed by the Specialized Component of Pharmaceutical Assistance of Piauí by patients with hemoglobinopathies. Fifty-two medication requests and laboratory tests presented by users were analyzed in light of the current Clinical Protocol and Therapeutic Guidelines (CPTG) with requests for renewal of the drug's receipt between June and August 2017. There was a prevalence of patients between 11-20 years (33 %), female (53%) and browns (59.6%). The majority of patients (33%) presented with only 2 LMEs authorized for treatment. The hemoglobin value increased in 48% of the 52 patients, with a mean of 8.57 g/dL to 8.61 g/dL and a significant increase in mean MCV between the patients before and after the use of HU. Neutropenia was observed in four patients prior to initiation of treatment and in eight patients in the course of their treatments with an average initial dose of 17.32 mg/kg/day in the prescriptions analyzed. It was observed that 10 of the 27 female patients had no results for the β-HCG test. The HIV serology test was no longer reported on 27 occasions. Hepatic, renal, uric acid and reticulocyte monitoring exams also ceased to be presented, especially prior to treatment. Half of the patients (n = 26) were diagnosed with ICD D57 and in 12 cases there was no attribution of ICD by the prescriber. The study demonstrated improvement in the hematological parameters of the patients, although, some aspects analyzed show differences with criteria established in the current CPTG.